ANALISIS PENGARUH LEARNING BEHAVIOR FROM FAILURE TERHADAP SUBJECTIVE WELLBEING DIMEDIASI OLEH ORGANIZATIONAL CRISIS PREPAREDNESS PADA UKM DI SUMATERA BARAT - Ariliusra, Azzukhruf; Games, Donard (LPPM Universitas Muhammadiyah Sumatera Barat, 2020)
This research was conducted aimed to determine the effect of learning behavior from failure on subjective wellbeing through organization crisis preparedness as a mediating variable. The method used in this study is quantitative, data collection by questionnaire, sampling is done by convenience sampling with a sample of 216 people but 200 questionnaires were returned. Data analysis techniques using structural equation models (SEM). The results obtained from this study indicate a negative relationship between learning behavior from failure and subjective wellbeing but do not have a significant effect, and from mediation analysis found no mediating influence through organizational crisis preparedness on learning behavior from failure with subjective wellbeing. Keywoed : Learning behavior from failure, organization crisis preparedness, subjective wellbeing, happiness